2006
DOI: 10.2105/ajph.2004.061606
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of Real-World Obstacles to Successful Cervical Cancer Prevention in Developing Countries

Abstract: Papanicolaou screening is feasible anywhere that screening for cervical cancer, the leading cause of cancer-related death among women in developing countries, is appropriate. After documenting that the Vietnam War had contributed to the problem of cervical cancer in Vietnam, we participated in a grass roots effort to establish a nationwide cervical cancer prevention program in that country and performed root cause analyses of program deficiencies. We found that real-world obstacles to successful cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 64 publications
0
58
0
1
Order By: Relevance
“…Public health is a typical area in which the prevailing approaches tend to locate problems within the biology and behaviour of the individual person while a systemic approach focuses attention on the wider processes and contexts that shape individual susceptibilities (Leischow and Milstein 2006). Particular studies have looked at adolescent obesity (Pronk and Boucher 1999), cervical cancer (Suba et al 2006), mental health (McCubbin and Cohen 1999), malaria control (Temel 2005) and maternal health (Parkhurst et al 2005). …”
Section: Medicine and Healthmentioning
confidence: 99%
“…Public health is a typical area in which the prevailing approaches tend to locate problems within the biology and behaviour of the individual person while a systemic approach focuses attention on the wider processes and contexts that shape individual susceptibilities (Leischow and Milstein 2006). Particular studies have looked at adolescent obesity (Pronk and Boucher 1999), cervical cancer (Suba et al 2006), mental health (McCubbin and Cohen 1999), malaria control (Temel 2005) and maternal health (Parkhurst et al 2005). …”
Section: Medicine and Healthmentioning
confidence: 99%
“…Both locally and globally, socio-political problems associated with sustaining working coalitions from groups with shared interests but competing incentives constitute critically important real-world obstacles to successful cervical cancer prevention and will remain so irrespective of the screening method(s) eventually used. In settings where health systems cannot afford to ignore such incentives, laboratory data constitute an essential yet sometimes overlooked fulcrum against which to leverage the social change required to preserve life (Suba et al, 2006) There is need for sensitisation of health workers about cervical cancer and importance of screening. Based on studies carried out in countries where organized screening is available, it is known that screening uptake can be influenced by cultural beliefs, the social position of women, characteristics of the health care system, the physician's attitudes towards screening and women's comprehension of the screening process.…”
Section: Improvements In Outlookmentioning
confidence: 99%
“…We need a greater focus on how interventions should be used in a complex behavioural environment, to better capture the dynamics of social networks and to understand how complex systems can adapt positively to change. This is a task where operational research and management science tools can be useful, as demonstrated by systems analysis of programmes for cervical cancer prevention 37 or agent simulation modelling of spread of HIV in villages. 38 Health systems are of course embedded in wider systems.…”
Section: Integrating Into Health Systemsmentioning
confidence: 99%